2021
DOI: 10.1523/jneurosci.3096-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 Regulates the Postnatal Acquisition of Peripheral Nerve Architecture

Abstract: Peripheral nerves are organized into discrete compartments. Axons, Schwann cells (SCs), and endoneurial fibroblasts (EFs) reside within the endoneurium and are surrounded by the perineurium, a cellular sheath comprised of layers of perineurial glia (PNG). SC secretion of Desert Hedgehog (Dhh) regulates this organization. In Dhh nulls, the perineurium is deficient and the endoneurium is subdivided into small compartments termed minifascicles. Human Dhh mutations cause a neuropathy with similar defects.Here we e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…S6 I-J). Notably, Schwan cells’ derived Desert hedgehog ( Dhh ) has been reported to regulate the structural and functional integrity of peripheral nerves (Parmantier et al, 1999; Sharghi-Namini et al, 2006; Zotter et al, 2022). Accordingly, Cldn1+ fibroblasts express the hedgehog pathway target genes Ptch1 and Gli1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6 I-J). Notably, Schwan cells’ derived Desert hedgehog ( Dhh ) has been reported to regulate the structural and functional integrity of peripheral nerves (Parmantier et al, 1999; Sharghi-Namini et al, 2006; Zotter et al, 2022). Accordingly, Cldn1+ fibroblasts express the hedgehog pathway target genes Ptch1 and Gli1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously suggested that the outer spindle capsule is part of the perineural sheath in the peripheral nervous system ( Shantha et al, 1968 ). Recently, Gli1 was shown to be expressed by perineural glial cells ( Zotter et al, 2022 ). Examination of our data showed that Gli1 transcripts were significantly upregulated in the muscle spindle samples as compared to the extrafusal fiber samples (log fold change 3.57; Supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notch and Hedgehog (Hh) were first described in Drosophila by Thomas Hunt Morgan in 1917 and by Nusslein-Volhard and Wieschaus in 1980 [1,2]. Both signaling pathways exist widely in vertebrates and invertebrates, are highly primordial and conserved in evolution, and are intimately involved in the fate determination of cells [3,4], differentiation of tissues [5], development of organs [2,[6][7][8][9], formation of embryos [10,11] and homeostasis in organisms [12]. Abnormalities in the modulation of both pathways during embryonic development may contribute to malformations [13][14][15] and disorders [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%